Does the establishment of civilized cities promote urban inclusive development?--Quasi-natural experiment based on the selection of "National Civilized City". - Enguang Zhang; Jing Zhang; Xuesi Li; Yangyang Dai; Mingdou Zhang; Weilu Li (PLoS ONE)
Taking the selection of "National Civilized City" as a quasi-natural experiment and basing on the research samples of 272 prefecture level and above cities in China from 2003 to 2020, this paper explores the impact of the establishment of civilized cities on urban inclusive development and its mechanism by using the time-varying DID model. The findings are as follows: firstly, the establishment of civilized cities has significantly promoted the urban inclusive development, and then parallel trend test, placebo test and other robustness tests verify the reliability of the research conclusions. Secondly, in regions with larger population, stronger financial strength and belonging to the Excellent Tourism City, the establishment of civilized cities has a more obvious role in promoting urban inclusiveness. Thirdly, the establishment of civilized cities promotes the urban inclusive development through government public regulation at the macro level, industrial structure upgrading at the middle level, and talent gathering and infrastructure construction at the micro level. The research conclusion of this paper has a certain reference value for giving full play to the policy effect of the selection of "National Civilized Cities", further promoting the urban inclusive development and achieving common prosperity.